PENGARUH MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN MATEMATIKA SISWA SEKOLAH DASAR : STUDI META-ANALISIS - Fatkhul Arifin; Tri Anjani Ashari; Fauzan Fauzan (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2021)
This study aims to determine the influence of the Problem Based Learning (PBL) learning model on the overall mathematics learning in several scientific journals at the basic education level